If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x(x + -5) = 5 Reorder the terms: 3 + -1x(-5 + x) = 5 3 + (-5 * -1x + x * -1x) = 5 3 + (5x + -1x2) = 5 Solving 3 + 5x + -1x2 = 5 Solving for variable 'x'. Reorder the terms: 3 + -5 + 5x + -1x2 = 5 + -5 Combine like terms: 3 + -5 = -2 -2 + 5x + -1x2 = 5 + -5 Combine like terms: 5 + -5 = 0 -2 + 5x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 2 + -5x + x2 = 0 Move the constant term to the right: Add '-2' to each side of the equation. 2 + -5x + -2 + x2 = 0 + -2 Reorder the terms: 2 + -2 + -5x + x2 = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5x + x2 = 0 + -2 -5x + x2 = 0 + -2 Combine like terms: 0 + -2 = -2 -5x + x2 = -2 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = -2 + 6.25 Reorder the terms: 6.25 + -5x + x2 = -2 + 6.25 Combine like terms: -2 + 6.25 = 4.25 6.25 + -5x + x2 = 4.25 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = 4.25 Calculate the square root of the right side: 2.061552813 Break this problem into two subproblems by setting (x + -2.5) equal to 2.061552813 and -2.061552813.Subproblem 1
x + -2.5 = 2.061552813 Simplifying x + -2.5 = 2.061552813 Reorder the terms: -2.5 + x = 2.061552813 Solving -2.5 + x = 2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 2.061552813 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 2.061552813 + 2.5 x = 2.061552813 + 2.5 Combine like terms: 2.061552813 + 2.5 = 4.561552813 x = 4.561552813 Simplifying x = 4.561552813Subproblem 2
x + -2.5 = -2.061552813 Simplifying x + -2.5 = -2.061552813 Reorder the terms: -2.5 + x = -2.061552813 Solving -2.5 + x = -2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -2.061552813 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -2.061552813 + 2.5 x = -2.061552813 + 2.5 Combine like terms: -2.061552813 + 2.5 = 0.438447187 x = 0.438447187 Simplifying x = 0.438447187Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.561552813, 0.438447187}
| 24k^2-31k-36=k | | 0.6(x-1.3)=.15 | | 27-4t-12t=t-7 | | X^2-5x-29=0 | | 12x+3x=100+22 | | 64=((2*h)*h)/2 | | 5x+5x=70 | | x^2-6-5x=0 | | -8m-3m=16 | | 64=(2h*h)/2 | | 7(4n-5m)= | | (8i)(4i)(9i)= | | 13x^2+44x+14=7x^2 | | (X-5y)(x+3y)= | | y=x^3-81x | | 3x^2-15-2x=0 | | 72=3(3z) | | 9(g-5h)= | | 10x-9y=2 | | 15x+7x-2=0 | | x+x+74=180 | | f(x)=3x^2+5x-7 | | 30=22.5/r | | (7x+3)(2x+6)=0 | | y=-x^2-10x+25 | | 10(b+4c)= | | 3x+34=9x-2 | | 1/(2sin(2x) | | 89-73=27y-31y | | 2x-(-4)=212 | | 2a+7=51 | | 2v-2=3v+15 |